Ecological Devastation in Annie Proulx’s Barkskins: A Byproduct of Capitalism - Shrestha, Ravi (Literary Studies, 2024)
This research article deals with the ecological devastation of a part of North America or New France (today’s Canada) colonized by France in the seventeenth and eighteenth centuries. The novel Barkskins on which the research is done is written by Annie Proulx, an American novelist. Firstly, the article reflects the portrayal of the environmental and ecological crisis of North America by European colonialists/capitalists. It shows Annie’s close observation of the chopping down of ancient American trees, the killing of wild animals, and the business of timber and fur by Europeans. Such commercial activities that reflect European capitalism cause the heavy loss of biodiversity. Their activities reflect their anthropocentric nature. Secondly, the article deals with how Native Americans encounter European capitalists. Even though they want to defend their true wilderness from the white Europeans, they prove to be weaker than the capitalists. However, their biocentric nature appears to be different from the anthropocentric nature of the European colonialists. So, one objective of the article is to discover how European capitalists/colonialists cause ecological devastation in North America. The second objective of the article is to examine why they demolish the true wilderness of North America and the third objective of the article is to scrutinize how the Native Americans react. Since the novel reflects the ecological crisis and the article deals with the impact of European capitalists/Colonists on ecology and the environment in North America, ecocriticism is a suitable theory to apply for textual analysis in the article. Hence, for a broad theoretical framework, Greg Garrard’s theory of Ecocriticism has been applied for textual analysis to explore how and why the biodiversity of North America has been affected since in Ecocriticism, Garrard’s definition of ecocriticism “Indeed, the widest definition of the subject of ecocriticism is the study of the relationship of the human and the non-human, throughout human cultural history and entailing critical analysis of the term ‘human’ itself” (5) becomes very contextual for textual analysis in the research.